Financial Development, Financial Fragility, and Growth - Loayza, Norman (IMF Working Papers; Working Paper ;, 2005)
This paper studies the apparent contradictions between two strands of the literature on the effects of financial intermediation on economic activity. On the one hand, the empirical growth literature finds a positive effect of financial depth as measured by, for instance, private domestic credit and liquid liabilities. On the other hand, the banking and currency crisis literature finds that monetary aggregates, such as domestic credit, are among the best predictors of crises and their related economic downturns. This paper accounts for these contrasting effects based on the distinction between the short- and long-run effects of financial intermediation.